Model Pembentukan Peraturan Perundang-Undangan Pasca Putusan Mahkamah Konstitusi Nomor 91/Puu-Xviii/2020 - Tibaka, Leli; Primayanti, Andi Dewi; Chalid, Idham; S, Irzha Friskanov. (Faculty of Law, Universitas Muhammadiyah Pontianak, 2023)
In actuality, the Constitutional Court's decision confirms that the Job Creation Law's formation is conditionally illegal, which means that the methods, strategies, and procedures used to create the Job Creation Law are against the Constitution. Given that article 22A of the constitution states that